Expectations and values about expanded newborn screening: a public engagement study. (1st February 2013) - Hayeems, Robin Z.; Miller, Fiona A.; Bombard, Yvonne; Avard, Denise; Carroll, June; Wilson, Brenda; Little, Julian; Chakraborty, Pranesh; Bytautas, Jessica; Giguere, Yves; Allanson, Judith; Axler, Renata
Abstract Objectives Newborn bloodspot screening (NBS) panels have expanded to include conditions for which treatment effects are less certain, creating debate about population‐based screening criteria. We investigated Canadian public expectations and values regarding the types of conditions that should be included in NBS and whether parents should provide consent. Methods Eight focus groups (FG; n = 60) included education, deliberative discussion and pre‐/post‐questionnaires. Data were analysed quantitatively and qualitatively. Results Quantitatively, the majority supported NBS for serious disorders for which treatment is not available (95–98, 82%). A majority endorsed screening without explicit consent (77–88%) for treatable disorders, but 62% supported unpressured choice for screening for untreatable disorders. Qualitatively, participants valued treatment‐related benefits for infants and informational benefits for families. Concern for anxiety, stigma and unwanted knowledge depended upon disease context and strength of countervailing benefits. Conclusions Anticipated benefits of expanded infant screening were prioritized over harms, with information provision perceived as a mechanism for mitigating harms and enabling choice. However, we urge caution around the potential for public enthusiasm to foster unlimited uptake of infant screening technologies.